When she is Standing Left, she Might be Blamed. Responsibility Attribution for Sexualized Violence Moderated by Rape Myth Acceptance and Benevolent Sexism. (February 2023) - Halicki, Katharina T.; Hauser, Robin; Wänke, Michaela
The present research contributes to the literature on victim blaming in cases of sexualized violence. Our findings show that even subtle cues, such as positioning in a picture, can influence blame attribution, particularly for people who are motivated to do so. In our experimental study we could show that with increasing rape myth acceptance as well as with increasing benevolent sexism, participants assigned more responsibility for later occurring sexualized violence to a woman displayed on the left-hand side compared to a woman displayed on the right-hand side of a picture.